Determination of certain substances in electrotechnical products. Simultaneous determination. Polybrominated biphenyls, polybrominated diphenyl ethers and phthalates in polymers by gas chromatography-mass spectrometry Part 12, (18th August 2023) - British Standards Institution,
No abstract available